(untitled) (Revista de Ciências Agroveterinárias, 2019)
The objective of this study was to estimate the optimal zinc and manganese levels for bone mineralization of broilers at 21 and 42 days of age, besides the methods comparison for quantifying the degree of bone mineralization, reliability test, execution time and effect of fat extraction, aiming to make feasible a more practical technical procedure in laboratory terms. In each experiment, 320 male chicks were housed in iron mesh metabolic cages, distributed according to a completely randomized experimental design in eight treatments with five replicates of eight birds each. In experiment 1, zinc sulfate was included at 0, 60, and 100 mg/kg and zinc methionine at 20, 40, 60, 80, and 100 mg/kg. In experiment 2, manganese sulfate was added at 0, 65, and 105 mg/kg and manganese methionine at 25, 45, 65, 85, and 105 mg/kg. The evaluated trace minerals (zinc and manganese) did not interfere in the evaluated bone characteristics, regardless of source or level. The degree of bone mineralization increased according to the concentration of zinc and manganese in the diet, regardless of source of these trace elements. The most appropriate method to determine the zinc and manganese content is with the use of tibias. There is no need to extract fat from the tibia to determine the zinc or manganese content, and the analysis can be performed with less time of execution without detriment of the results.